Knowledge of Nurses Regarding Essential Newborn Care in Special Care Neonatal Units (SCANU) of Different Hospitals of Chattogram, Bangladesh - Sharmin, Tasnuva; Chowdhury, Pranab Kumar; Khan, Tafazzal Hossain; Hoque, Md Obidul (Journal of Bangladesh College of Physicians and Surgeons, 2021)
Background: The advancements in intensive care in recent decades have enabled better survival of newborn. Knowledge of essential newborn care is important for the survival, growth, and development of a newborn. In spite of its essentiality, most health-care professionals do not know and follow the World Health Organization recommendation. Aim and objectives: The aim of this study was to assess the knowledge of nurses regarding essential newborn Care in Special Care Neonatal Units (SCANU). Materials and methods: This observational study was conducted among the nurses working in SCANU of Chattogram Medical College and Hospital, Chattogram Maa- O- Shishu Hospital and Bangabandu memorial hospital of University of Science and Technology, Chattogram (USTC) for 6 months. Purposive sampling technique were applied for selecting the sample. A structured data sheet was predesigned to collect data. Knowledge regarding Essential Newborn Care among the nurses graded as satisfactory or not satisfactory. Results: In this study it was observed that 69.0% nurses had completed diploma in nursing and midwife education, B. Sc in nursing 11.0%, diploma in nursing 7.0%. 56.0% nurses attended special courses/training in neonatology. 94.75% of the nurses had satisfactory knowledge regarding essential newborn care. 58.0% of nurses washed their hands with disinfectant solution before handling the baby, 99.0% mentioned that the baby must be breast feeding within 1st hour of delivery, 92.0% mentioned that baby must be fed 6 months of exclusive breast feed, 91.0% knew how to stabilize body temperature of low birth weight newborn. The knowledge regarding essential newborn care were almost similar with age, gender, religion, marital status, educational level, working place and attending special courses/training in neonatology. Conclusion: Most of the nurses working in SCANU of both Government and non-government hospitals of Chattogram have good knowledge regarding ENC. This knowledge appeared irrespective of their age, gender, religion, marital status, working place and special courses/training in neonatology. J Bangladesh Coll Phys Surg 2021; 39(3): 185-192